Performa dan Karakteristik Emisi Gas Buang Mesin Diesel Berbahan Bakar Ganda - Arifin Siagian; Mawardi Silaban (Jurnal Teknik Mesin (Sinta 3), 2011)
Today’s the global warming of the earth and atmospheric pollution caused by combustion engines has become a social problem. Further more, the dependence on fossil fuels is expected to be reduced, and therefore more expensive, because of dwindling availability. This paper discusses on a conventional diesel engine, i.e., compression ignition piston combustion engine (compression ignition) that related to the polution and efficiency. A diesel engine is operated by injecting a bit of diesel as a trigger ignition only, Fuel Gas (CNG) as fuel staple together the air flow through the mixer in the intake port into the cylinder combustion engine. In this case the engine performance test using each of the two types of fuel gas, ie propane (C3H8) and hydrogen (H2), with a percentage that varies. For comparison, the operation of the engine with standard fuel (diesel 100%, single-fuel) were also performed. This performance test includes analysis of the pressure in the cylinder, exhaust gas emission characteristics, and thermal efficiency. Heat release rate (rate of heat release) was calculated from the derivative of the pressure measurement results in the cylinder. As a result, it has been known that; exhaust emissions on operating conditions with both gas fuel (propane and hydrogen), each of which produce smoke (smoke or soot or Particulate Matter, PM), hydrocarbons (HC), carbon monoxide (CO), carbon dioxide (CO2) and nitrogen oxides (NOx), which decreased significantly, but the thermal efficiency slightly decreased.